New contributions to propagation of pineapple (Ananas comosus L. Merr) in temporary immersion bioreactors - Gonzalez-Olmedo, J.L.; Fundora, Z.; Molina, L.A.; Abdulnour, J.; Desjardins, Y.; Escalona, M.
Plantlets propagated in temporary immersion bioreactors (TIB)have better performance than those propagated by conventional methods such as micropropagation. This is as a result of a better handling of the in vitro atmosphere and the nutrition. The object of this study was to further improve the cultivation conditions by introducing photomixotrophism as an intermediate link of photoautotrophic growth during ex vitro cclimatization. For this purpose the effects of light were evaluated by different parameters such as photosynthetic photon flux density (PPF), sucrose concentration, and CO2 enrichment levels on CO2 evolution inside the culture vessels. It was observed that CO2 diminished upon light exposure and increased in the dark according to the photoperiod during each cycle of immersion. With this approach it was possible to increase the photomixotrophism in the pineapple plantlets propagated in TIB. It was demonstrated that light is the factor with more influence on plant quality, although under these conditions they seem to use more of the nutrients of the medium than their photoassimilates. The propagation of pineapple in TIB involves three phases: proliferation, pre-elongation, and final growth of the buds. In each phase the cultivation conditions were determined to substitute for sterilization by autoclaving, to improve the quality of the plants, to elevate the efficiency of the process, and to reduce production costs. The buds that grew in the temporary immersion bioreactor with the presence of Vitrofural (G-1)achieved the best indicators of growth. Significant increases were observed in the leaf area, dry mass of the buds, and chlorophyll contents.
Keywords: PHOTOMIXOTROPHISM; PLANT QUALITY; STERILIZATION